Information Technology Supports for Student-Centered Language Education - Feketéné Silye, Magdolna (Acta Agraria Debreceniensis, 2003)
With the development of computer-mediated communication, the definition of literacy has gained broader dimensions (Murray, 1991). The ability to use new technologies to access, adapt and make intelligent use of information and knowledge is by now viewed as an additional and essential component of literacy. Today’s interpretation of literacy (often referred to as “multiliteracy”) must incorporate the communication that takes place through a growing variety of text forms associated with information and multimedia technologies.Since it is fast becoming a basic instrument for building the literacies required for success in academic and workforce environments, used as a tool, information technology needs to become a critical component of student-centered English language education.